PH-sensitive polymeric nanoparticles for tumor-targeting doxorubicin delivery: concept and recent advances. (March 2014) - Meng, Fenghua; Zhong, Yinan; Cheng, Ru; Deng, Chao; Zhong, Zhiyuan
Doxorubicin is a potent chemotherapeutic drug applied in the clinics for the treatment of various human cancers. It is typically administered as the hydrochloride salt or in liposomal forms, which are plagued with severe side effects. In recent years, pH-sensitive polymeric nanoparticles that are capable of retaining drug during circulation while actively releasing it at the tumor site and/or inside the target tumor cells have received an overwhelming interest for tumor-targeting cancer chemotherapy. This smart delivery approach has shown to elegantly resolve the in vivo stability versus intracellular drug release dilemma, as well as stealth versus tumor cell uptake dilemma. In this review, the concept and exciting new advances in pH-sensitive polymeric nanoparticles for doxorubicin delivery are presented and discussed.